Aktivitas Sitotoksik Ekstrak Etanol, Fraksi Etanol-Air, Etil Asetat serta N-Heksana Buah Pare (Momordica charantia) pada Sel MCF-7 secara In-Vitro - Adhe Retnantya Pamungkas; Peni Indrayudha (Pharmacon: Jurnal Farmasi Indonesia, 2019)
Bitter melon is one of fruit that have pharmacological effects such as an anticancer which potentially active on breast cancer cell MCF-7. The aim of this study was to compare the potential cytotoxic activity between ethanol extract of pare and the results of ethanol, ethyl acetate and n-hexane fraction on MCF-7 breast cancer cells and to determine the class of compounds contained in each sample. Pare’s powder was extracted with maceration method in 80% ethanol solvent and then continue to fractionated in 96% ethanol, ethyl acetate and hexane solvent. Extract and fractions were continue to cytotoxic assay using the MTT assay method. Cytotoxic test results showed that the ethanolic extract had no potential cytotoxic activity. Ethyl acetate fraction with the highest concentration 16 µg/mL has the highest potential inhibition 43,87% on MCF-7 cells population. Extract and fractions than continue to phytochemical screening with Thin Layer Chromatography (TLC) method. TLC detection showed that n-hexane fraction contained more compound groups than ethanolic extract, ethanolic-water fraction and ethyl acetate fraction.